A mixed phase-field fracture model for crack propagation in punctured EPDM strips. (October 2021) - Mang, Katrin; Fehse, Andreas; Kröger, Nils Hendrik; Wick, Thomas
Abstract: In this work, we present crack propagation experiments evaluated by digital image correlation (DIC) for a carbon black filled ethylene propylene diene monomer rubber (EPDM) and numerical modeling with the help of variational phase-field fracture. Our main focus is the evolution of cracks in one-sided notched EPDM strips containing a circular hole. The crack propagation experiments are complemented with investigations identifying the mechanical material properties as well as the critical strain energy release rate. For simulating the evolution of cracks with a given notch, phase-field fracture modeling is a popular approach. To avoid volume-locking effects considering fractures in nearly incompressible materials, a quasi-static phase-field fracture model in its classical formulation is reformulated with the help of a mixed form of the solid-displacement equation. The newly established mixed phase-field fracture model is applied to simulate crack propagation in punctured EPDM strips by using the experimentally identified material parameters with mixed finite elements. To discuss agreements and point out challenges and differences, the crack paths, the maximal force response, the traverse displacement at the crack start, as well as force–displacement curves of the experimental and numerical results are compared. Highlights: Determining the material compounding and properties as well as the (critical) strain energy release rate of EPDM rubber via digital image correlation (DIC). Deriving a quasi-static mixed phase-field fracture model based on Wu's model and Amor's strain energy splitting for incompressible solids. Applying and substantiating the new model via numerical simulations of crack propagation in punctured EPDM strips.